Pulmonary antimicrobial photodynamic therapy and the role of the lung surfactant - Kassab, Giulia (2022)
Pneumonia is one of the largest causes of death worldwide and antimicrobial photodynamic therapy (aPDT) has been proposed as a broad-spectrum, resistance-proof treatment alternative for it. The initial objective of this study was to demonstrate the efficacy of indocyanine green (ICG)-based aPDT against multiple pathogens and its safety in different animal models. In vitro, the aPDT protocol successfully inactivated two strains of S. aureus, while showing no cytotoxicity to three different mammalian cell lines. In vivo, mice that received the treatment showed no signs of tissue damage or inflammation. However, the in vivo treatment of bacterial pneumonia was unsuccessful, despite multiple attempts in three different models. Further investigation of the interaction between photosensitizers and the pulmonary microenvironment showed that photosensitizers interact with the lung surfactant. This interaction does not inhibit the generation of reactive oxygen species, but instead distances them from the bacterial target, leading to a loss of activity. The clinical lung surfactant Survanta® decreases the aPDT effect of ICG, Photodithazine®, bacteriochlorin-trizma and protoporphyrin IX against S. pneumoniae. Methylene blue (MB) did not lose efficacy in this experimental setup, but its activity was quenched in the in vitro alveolar model, in which the localized concentration of lung surfactant is higher. Surface chemistry-based experiments revealed that ICG has a strong surface activity and interacts strongly with Survanta® and LPS. MB is not surface-active but has some interaction with Survanta® if mixed directly into it. The nanoemulsions neMB and nePS exhibit surface-activity as they slowly break into single molecules on the surface, and interact with the multilayered Survanta®. We have established the importance of the lung surfactant in the development of pulmonary aPDT and propose that formulation strategies can be used to overcome the lung surfactant barrier. ICG remains the most promising candidate for pulmonary PDT because of its safety and excitation range, and preliminary results indicate that combining it with the perfluorocarbon PFOB might be a viable alternative for the treatment of in-hospital patients. Additionally, preliminary results with a MB nanoemulsion have been promising and might aid the development of new pulmonary photosensitizers in the future.